INOVASI PENGEMBANGAN MATERI PELAJARAN BAHASA ASING TINGKAT MADRASAH TSANAWIYAH BERBASIS WHITEBOARD ANIMATION - Najahah Najahah; Ulin Ni'mah Rodliya Ulfah (Al'Adalah, 2020)
Technology and foreign language are two related things. Mastery in the above two is a must for academic people, either for the teachers or the students. It is because, majority, the learning activity are done with the help of digital technology and foreign language. Technology is created in order to help human activity and also to improve the goals’ achievement. While in the teaching and learning process, students tend to understand the material more if it is delivered in the form of a picture, movie, video or animation. Foreign learning, nowadays, is considered unsatisfied since the material delivered is monotone and less in touch with the technology, so it is not really attractive. Second, the learning materials are associated more with a textbook. While actually, the learning materials can be in the form of a dictionary, cassette, video, worksheet and so on. Based on the above fact, the researcher improves the foreign (English and Arabic) learning materials for Islamic Junior High School based on whiteboard animation.